Racial Disparities in Incidence of Diaper Dermatitis and Implications for Diaper Inequities - Jennifer Randles; Justin van Zerber; Kristian Browning; Balaraman Rajan; Benito Delgado-Olson (Health Equity)
Objectives: To examine if the likelihood of infants and toddlers requiring medical care for diaper dermatitis, a condition linked to infrequent diaper changes and possible diaper need, is different across racial/ethnic groups. Materials/Methods: This is a population-based retrospective study. We collected data via public records requests from the California Department of Health Care Access and Information to determine the number of patients aged 0 to 3 years diagnosed with diaper dermatitis from 2010 to 2021 in emergency departments (EDs) and hospitals. We used two sample t-tests to compare the incidences of ED visits and in-patient hospitalization during the 11-year time period to identify differences across racial/ethnic groups. Results: From 2010 to 2021, there were 184,097 total diagnoses of diaper dermatitis, 53,678 of which received in-patient treatment. The annual mean was 15,341 and ranged between 9,407 and 17,425. The prevalence (per 1,000 children aged 0–5 of the respective race) was highest for the Black population averaging 9.56 (range: 5.79 to 11.37). The prevalence was 5.93 (3.75 to 7) for the White population, 2.49 (1.78 to 3.14) for Asian/Pacific Islanders, and 6.67 (4.25 to 7.52) for the Hispanic population. We find that Black children were disproportionately diagnosed with diaper dermatitis in California hospitals and EDs (p < 0.001). Conclusions: Racial disparities in medical conditions that can result from lack of sufficient diapers point to diaper need as a social determinant of health deserving of greater public attention and policy redress.